Status and Non-status Consumers' Attitudes toward Foreign and Domestic Luxury Brands of Underwear - Lee, Thomas; Phau, Ian; Roy, Rajat (Routledge, 2012)
This study investigates whether status- and non-status-seeking consumers differ in their attitudes toward buying foreign and domestic luxury brands of underwear with regard to their countries of manufacture. The findings indicate that while there is no significant difference for products made in Australia and the U.S. for both status- and non-status-seeking consumers, luxury brands of underwear made in China are not favored. The study suggests that China should improve its country image in order to be perceived as producing goods that are not only low in price but high in quality. The study also notes that American underwear brands with a strong global presence should consider production in the Australian market.